The `new clothes' of administrative control of information-providing organizations in Cameroon since the 1990 reform - Ndam, Gerard Pekassa (2004)
The aim of the present study is to examine whether the new political dynamism and legislative architecture of Cameroon in terms of communication has been accompanied by innovations in the administrative control of organizations providing information to describe the essence thereof. Analysis shows that the new political impetus towards democratization and the new legislative environment of liberalization have a definite influence on the practices of authorities vested with the power of administrative control. However, in the new legislative context resulting from Law 90-52, subsequent modifications and application regulatory texts, the control of information-providing organizations remains a major preoccupation of the administrative authorities and there have been changes. The 1990 reform regarding communication in Cameroon, of which Law 90-52 of 19 December 1990 regarding social communication constitutes the legal base, is ambiguous. Regardless of the advances that can be attributed to it, its scope appears to be limited. It is undeniable that this reform ushered in a new era. However, it must be noted that the liberalization in question was delimited. Far from being a `legal revolution', the reform of December 1990 offers the prospect of less cumbersome administrative control on information-providing organizations because it is dependent upon the slow rate of democratization of the national political system. - Reproduced.
Keywords: Administrative reform